Needs Analysis of Blind Students in Teaching Practice Program - *, Iswahyuni; Junining, Esti; Dewi, Dian Novita; Linta, Alies Poetri; Suwarso, Pratnyawati Nuridi (Sebelas Maret University, 2016)
As an inclusive university, Brawijaya University has accepted students with special needs in some differentstudy programs. Two of those are blind / visually impaired students who enrol English Language EducationStudy Program in which the program prepares the students to be English teachers. As a consequence, thestudents must be ready to do teaching practice in a public school when they are in the seventh semester. Thisstudy is going to find out the problems of the visually impaired students in conducting teaching practice in theschool. It also elaborates the teaching media and method that they need to support them to do teachingpractice.Â The method used in this study is descriptive qualitative. To get the data, the researchers interviewthe visual impairments, the two volunteers who become their peer assistant them during learning process inthe university, and the lecturer who becomes the advisor of the visually impaired students. Besides,observation is also important to know the application of teaching practice in their real class. The observationis done by recording the teaching activity conducted by the visually impaired students. The results of theinterview and the observation are used to formulate the needs of the visually impaired students in teachingprocess in the real school. This study gives benefit not only for the students in preparing their teachingpractice, but also for the institution to accommodate the needs of the visually impaired students for theirteaching process.